Analisis penataan arsip dinamis berbasis digital di Perpustakaan Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Agus Fandi (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2022)
This study aims to determine the management of dynamic archives carried out digitally by the UIN Syeh Ali Hasan Ahmad Addary Padangsidimpuan Library work unit. This study uses a qualitative descriptive with an interactive model. Data analysis starts from data reduction, data presentation, and drawing conclusions. Research informants are employees of dynamic archive management at the UIN Syeh Ali Hasan Ahmad Addary Padangsidimpuan Library work unit who were selected by snowball sampling technique. The findings of this study explain that the process of organizing digital-based archives is still in the planning and testing stages. In the arrangement of digital archives, there are three stages, namely filing, borrowing, and destroying archives. Although the UIN Syeh Ali Hasan Ahmad Addary Padangsidimpuan Library work unit has tested digital-based arrangements, the archive creation process still uses a manual system. Next is the archive borrowing stage, if there are borrowers from outside parties, they must fill out the digital archive system menu. This is so that the status of the archive can be known easily whether the archive is available or still borrowed. The third stage is archive destruction. The UIN Syeh Ali Hasan Ahmad Addary Padangsidimpuan Library work unit has carried out the destruction according to the archive retention schedule that has been determined. Thus, the development of digital-based archive arrangement is needed by the work unit so that the archive arrangement process can be more effective and efficient in providing services to the academic community, especially at this time.